A Synthesis of the Sustainability of Remedial Reading Intervention Effects for Struggling Adolescent Readers. (May 2021) - Daniel, Johny; Capin, Philip; Steinle, Paul
A majority of reading-related intervention studies aiming to remediate struggling readers' reading outcomes assess student performance immediately following the conclusion of an intervention to determine intervention effects. Few studies collect follow-up data to measure the long-term sustainability of treatment effects. Hence, the aim of the current synthesis was to examine follow-up intervention effects of reading interventions involving adolescent struggling readers in Grades 6 to 12. Our literature search yielded only 10 studies that reported follow-up data for intervention participants, which highlights the dearth of intervention research that examines sustainability of intervention effects. Of the 10 included studies, the weighted mean effect size for all reading outcome measures was gw = 0.78 at immediate posttest and gw = 0.27 at follow-up, in favor of treatment group students. Although the magnitude of difference between treatment and control groups diminished at follow-up time, a comparison of treatment group students' immediate posttest and follow-up scores showed that students mostly maintained gains made during intervention at follow-up time points.